A multicentre prospective randomized equivalence trial of a soft bandage and immediate discharge versus current treatment with rigid immobilization for torus fractures of the distal radius in children: protocol for the Forearm Fracture Recovery in Children Evaluation (FORCE) trial. (8th June 2020) - Achten, Juul; Knight, Ruth; Dutton, Susan J.; Costa, Matthew L.; Mason, James; Dritsaki, Melina; Appelbe, Duncan; Messahel, Shrouk; Roland, Damian; Widnall, James; Perry, Daniel C.
Abstract : Aims: Torus fractures are the most common childhood fracture, accounting for 500, 000 UK emergency attendances per year. UK treatment varies widely due to lack of scientific evidence. This is the protocol for a randomized controlled equivalence trial of 'the offer of a soft bandage and immediate discharge' versus 'rigid immobilization and follow-up as per the protocol of the treating centre' in the treatment of torus fractures . Methods: Children aged four to 15-years-old inclusive who have sustained a torus/buckle fracture of the distal radius with/without an injury to the ulna are eligible to take part. Baseline pain as measured by the Wong Baker FACES pain scale, function using the Patient-Reported Outcomes Measurement Information System (PROMIS) upper limb, and quality of life (QoL) assessed with the EuroQol EQ-5D-Y will be collected. Each patient will be randomly allocated (1:1, stratified by centre and age group (four to seven years and ≥ eight years) to either a regimen of the offer of a soft bandage and immediate discharge or rigid immobilization and follow-up as per the protocol of the treating centre. Results: At day one, three, and seven, data on pain, function, QoL, immobilization, and analgesia will be collected. Three and six weeks after injury, the main outcomes plus data on complications, resource use, and school absence will be collected. The primary outcome is the Wong-Baker FACES pain scale at three days post-randomization. All data will be obtained through electronic questionnaires completed by the participants and/or parents/guardian. Cite this article: Bone Joint Open 2020;1-6:214–221.